Ionic mass transfer on fixed disk and conical electrodes under streaming solutions : III. A second experimental approach and kinetic application - Bazán, Julio César (1967)
The rate of ionic mass transfer on fixed disk electrodes under streaming solutions was studied avoiding as far as possible any wall effect on the mass-transfer rate. Nickel electrodes, previously activated, and platinum and graphite electrodes with solutions of potassium ferro- and ferricyanide in sodium hydroxide were used. The geometry of the cell and other variables of the system were conveniently changed. The experimental rate equation agrees with that found by solving the Navier-Stokes and Fick's differential equations, for results with activated nickel electrodes, the fluid velocity being properly defined. Results obtained with platinum and graphite electrodes present a deviation from those equations, a fact which is interpreted in terms of an electrochemical reaction with intermediate kinetics. The kinetic parameters of the corresponding electrochemical reactions are evaluated.